Analisis Sistem Akuntansi Keuangan Daerah dalam Menentukan Kualitas Laporan Keuangan di Kabupaten Jayapura - Gratiana D.H.D Puspita; Apner Siang; Taufik Rachman; Alfida Dogopia (Departement of Mathematics Education, 2023)
This study aims to analyze the influence of the implementation of the regional financial accounting system, human resource competence and internal control systems on the quality of financial reports at the Jayapura Regency Social Service, both partially and simultaneously. This research was carried out at the Jayapura Regency Social Service office. The research will be carried out for more than 1 month. The source of data in this study is in the form of primary data obtained directly from the respondents or the samples in this study and data secondary sourced from information at research sites, scientific journals, sites or documents related to research objects. Data analysis in this study used quantitative data analysis, descriptive statistics, tests classical assumptions, multiple regression analysis, hypothesis testing with simultaneous tests (F-test) and partial tests (T-test) and the coefficient of determination using the SPSS application. The number of samples used were all employees, totaling 35 respondents. The results of the study proved that partially the regional financial accounting system had a significant effect on the quality of the social service financial reports for the Jayapura district, the competence of human resources did not have a significant effect on the quality of the financial reports for the Jayapura district social service and the system internal control has no significant effect on the quality of the financial reports of the Jayapura district social service. Simultaneously, the regional financial accounting system, human resource competency and internal control systems affect the quality of social service financial reports jayapura district.